THE EFFECT OF HEALTH EDUCATION USING BOOKLETS ON THE ATTITUDE OF WOMEN OF RELIABLE AGE ABOUT EARLY DETECTION OF CERVIC CANCER USING IVA TEST METHOD AT UPT PUSKESMAS ISLAND MERBAU REGENCY OF MERANTI ISLANDS - Fathunikmah, Fathunikmah; Lailiyana, Lailiyana; Laila, Ani; Az Zahra, Afifah Amani (Poltekkes Kemenkes Riau Under Health Ministry Republik Indonesia, 2025)
The achievement target for early detection of cervical cancer using the iva test method is 80%, while the coverage of early detection of cervical cancer using the iva test method in the Work Area of UPT Puskesmas Pulau Merbau is only 0.4%. Health education is one of the things needed to improve wus attitudes towards early detection of cervical cancer with the iva test method. One of the media that can be used is booklet. The purpose of this study was to determine the effect of health education using booklet media on wus attitudes about early detection of cervical cancer with the iva test method at the UPT Puskesmas Pulau Merbau, Meranti Islands Regency in 2022. This study was a quantitative study with a quasi-experimental type of research with a onegroup pretest - posttest design. design. The population in this study were all wus who visited the Puskesmas and Pustu in March 2022. The sampling technique was purposive sampling as many as 15 women of childbearing age. Collecting data using a questionnaire. Univariate and bivariate data analysis used the Wilcoxon test to determine the effect of attitudes on women of childbearing age between before and after the intervention. The results of statistical tests showed that there was an effect of health education using booklet media on wus attitudes about early detection of cervical cancer using the IVA sest method (p value = 0.001). It is suggested to midwives and cadres in Pulau Merbau sub-district to conduct health education to women of childbearing age by using booklet media so that wus attitudes become better and willing to carry out early detection of cervical cancer with the iva test method.